John Q - Cassavetes, Nick (New Line Cinema, 2002)
This suspense drama story centers on a man whose nine- year- old son is in desperate need of a life-saving transplant. When he discovers that his medical insurance won't cover the costs of the surgery and alternative government aid is unavailable, John Q. Archibald (Washington) takes a hospital emergency room hostage when he was left with no option to save his child. With the clock ticking, the hostage situation nears the surprising end as a desperate J.Q. must decide how much father his own heart can take him.